Fleets Go Green - Herrmann, Christoph; Mennenga, Mark Stephan; Böhme, Stefan (Sustainable Production, Life Cycle Engineering and Management, 2018)
The book presents the results of the research project Fleets Go Green from different engineering disciplines. It includes comprehensive empirical data as well as different methods and tools for evaluating and integrating electric vehicles into corporate fleets. Finally, the authors give recommendations for fleet owners, vehicle manufacturers and political decision. The aim of the joint research project Fleets Go Green was the integrated analysis and evaluation of the environmental performance of electric and plug-in-hybrid vehicles in everyday usage on the example of fleet operations. The potential of electric vehicles for reducing the harmful environmental impacts of road transport in everyday conditions can only be analyzed and evaluated in field tests. If electric vehicles should realize their potential to reduce emissions and minimize the consumption of resources, an integrated life cycle assessment is required.